Analisis Faktor Penyebab Turunnya Minat Penumpang dan Minimnya Aktivitas di Bandar Udara H. Asan Sampit - Seran, Maria Indriani Sofia; Dyahjatmayanti, Dhiani (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The purpose of this research is find out the causes of the decline in passenger interest and the lack of activity at Sampit H. Asan Airport. This study uses a qualitative research method which is conducted in September 2022 at H. Asan Sampit Airport, Central Kalimantan. This research was conducted using data collection techniques and data collection through interviews conducted with 4 informants, namely the Head of Class II H. Asan Sampit Airport, the Head of the Service and Cooperation Section, the General Manager of Wings Air, and passengers at H. Asan Sampit Airport, through observation and documentation. To test the validity of the data, researchers used a data credibility test which was carried out by triangulation of technical data. For data analysis that researchers use, namely, data reduction, data presentation, conclusion, and verification. The research results obtained from this study are the factors causing the decline in passenger interest in H. Asan Sampit Airport flight routes, where visitors and prospective passengers want additional flight routes, especially the islands of Kalimantan and Java. Facilities, where many passengers want facilities in the form of seats at the terminal and ticket prices, where passengers want promos for ticket prices at Sampit H. Asan Airport. The factor causing the lack of activity at H. Asan Sampit Airport is the lack of interest of passengers at H. Asan Sampit Airport which is caused by flight routes where there are only 2 routes at H. Asan Sampit Airport, the facilities at the terminal are incomplete and there are no promos for ticket prices at Sampit H. Asan Airport. Keywords: Factor ; Passenger Interests ; Airport Activity.